Возможности и перспективы использования технологии связанных данных в Президентской библиотеке - Жлобинская, Ольга Николаевна (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
The article discusses approaches to publishing library data of the Presidential Library in the LOD (Linked open data) environment as an integral part of a single digital knowledge space. The basic model of data is built taking into account the specifics of the Presidential Library catalogue: the integrated library cata-logue includes library, archival and museum materials; when building the catalog, the national RUSMARC format is used. The proposed scheme for publishing linked data is based on the transformation of MARC records using the IFLA LRM and RiC-CM conceptual models as well as standard ontologies.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական հանդես ։ Հատուկ թողարկում / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- էջ 116 - 119
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն